THE URGENCY OF THE PRENUPTIAL AGREEMENT FOR HUSBAND AND WIFE IN INDONESIAN MARRIAGE LAW - Deddy Gunawan (Journal Philosophy of Law, 2021)
This study aims to determine the prenuptial agreement on the separation of assets in marriage carried out by husband and wife in marriage law in Indonesia. Divorced married couples will fight over the separation of joint assets. This can be deviated by making a prenuptial agreement. The problems in this study are (1) How is the prenuptial agreement on the separation of assets in marriage? (2) What is the urgency of a prenuptial agreement for husband and wife in marriage law in Indonesia? This research is normative juridical, namely legal research using library materials by analyzing various provisions of the law or by using secondary data. The study results indicate that (1) a prenuptial agreement on the separation of assets in a marriage is carried out by both parties with mutual consent and can enter into a written agreement legalized by the marriage registrar. The agreement takes effect from the moment the marriage takes place. (2) The urgency of a prenuptial agreement for husband and wife in marriage law in Indonesia can be made before the marriage occurs. Since the decision of the Constitutional Court Number 69/PUU-XIII/2015, a marriage agreement can be made as long as it is within the marriage bond, as long as it does not violate applicable legal rules, religious rules, and moral norms. Husband and wife can express their will and agree on assets to carry out the pooling of assets and separation of assets.